Upaya Pemerintahan Daerah Dalam Menumbuhkan Inovasi Sosial - Adi Suhendra; Dyah Kusuma Wardani (Jurnal Kebijakan Pembangunan, 2018)
This research is driven by the existence of a new paradigm in solving problems in society in their social environment. Local governments make various breakthroughs to solve these problems with regional innovations. The purpose of this research is to determine the description of the government's efforts in spreading innovation in solving problems in the community. This study uses a qualitative case study approach. Triangulation of data sources is to explore the truth of certain information through various methods and sources of data acquisition. Data collection techniques are carried out by conducting in-depth interviews, secondary data collection, and observation. While data processing is performed by the data reduction. The reason for choosing this method is because this study is a special study that examined the research' subjects specifically. With this method, researchers can conduct observations and in-depth interviews with research subjects. The results shows that, regional innovations can be used as an efforts of regional governments in suppressing infant mortality, social protection and rehabilitation of women, and inclusive treatment for people with disabilities. Abstrak Penelitian ini dilatarbelakangi oleh adanya paradigma ba ru dalam penyelesaian masalah dimasyarakat dalam lingkungan sosialnya.Pemerintah daerah melakukan berbagai terobosan untuk dapat menyelesaikan permasalahan itu dengan inovasi daerah.Tujuan penelitian ini adalah untuk mengetahui gambaran upaya pemerintah dalam menyebarkan inovasi dalam penyelesaian masalah di masyarakat.Penelitian ini menggunakan pendekatankualitatif studi kasus. Triangulasi sumber data adalah menggali kebenaran informasitertentu melalui berbagai metode dan sumber perolehan data. Teknik pengambilan data dilakukan dengan melakukan wawancara mendalam, pengumpulan data sekunder, dan observasi.Sedangkan pengolahan data dilakukan dengan carareduksi data.Alasan pemilihan metode ini adalah kajian ini merupakan kajian khusus yang memahami obyek ditelitinya secara khusus.Dengan metode ini, peneliti dapatmelakukan pengamatan dan wawancara mendalam dengan subyek penelitian.Hasil yang di dapatkan adalah inovasi daerah dapat dijadikan sebuah cara bar u terhadap upaya pemerintahan daerah dalam Menekan Angka Kematian Bayi, Perlindungan dan Rehabilitasi Sosial Bagi Wanita, Penanganan Inklusif Untuk Kaum Difabel.